Qualification of a whole blood intracellular cytokine staining assay to measure mycobacteria-specific CD4 and CD8 T cell immunity by flow cytometry - Kagina, Benjamin M.; Penn-Nicholson, Adam; Sidibana, Mzwandile; Kaplan, Gilla; Hanekoma, Willem A.; Scriba, Thomas J. (Journal of immunological methods, 2015)
Qualified or validated assays are essential in clinical trials. Short-term stimulation of whole blood and intracellular cytokine staining assay is commonly used to measure immunogenicity in tuberculosis vaccine clinical trials. Previously, the short-term stimulation process of whole blood with BCG was optimized. We aimed to qualify the intracellular cytokine staining process and assess the effects of long-term cryopreservation. Our hypotheses were that the assay is robust in the measurement of the mycobacteria-specific T cells, and long-term cryopreservation of fixed cells from stimulated whole blood would not compromise reliable measurement of mycobacteria induced CD4 T cell immunity. Whole blood from healthy adults was collected in sodium heparinized tubes. The blood was left unstimulated or stimulated with mycobacterial antigens or mitogens for 12h. Cells were harvested, fixed and multiple aliquots from each participant cryopreserved. Later, mycobacteria-specific CD4 and CD8 T cells expressing IFN-γ, TNF-α, IL-2 and IL-17 were quantitated by flow cytometry. Assay performance characteristics evaluated included limit of quantification and detection, reproducibility, precision, robustness, specificity and sensitivity. To assess the effects of long-term cryopreservation, fixed cells from the stimulated bloods were analysed one week post-cryopreservation and at 3-month intervals over a 3-year period. The limit of quantification for the different cytokines was variable: 0.04% for frequencies of IFN-γ- and IL-2-expressing T cells and less than 0.01% for TNF-α- and IL-17-expressing T cells. When measurement of the mycobacteria-specific T cells was assessed at levels above the detection limit, the whole blood intracellular cytokine assay showed high precision that was operator-independent. The assay was also robust: variation in staining conditions including temperature (4°C or 20–23°C) and time (45, 60 or 90min) did not markedly affect quantification of specific T cells. Finally, prolonged periods of cryopreservation also did not significantly influence quantification of mycobacteria-specific CD4 T cells. The whole blood intracellular cytokine assay is robust and reliable in quantification of the mycobacteria-specific T cells and is not significantly affected by cryopreservation of fixed cells.
Keywords: Qualification; Whole blood; Intracellular cytokine staining assay; Flow cytometry